Convenient or risky? Investigating the behavioral intention to use facial recognition payment in smart hospitals - Teng Yu; Ai Ping Teoh; Chengliang Wang; Qing Bian (Humanities & Social Sciences Communications)
Abstract This study investigates the factors influencing users’ behavioral intention to adopt facial recognition payment (FRP) in smart hospitals, considering convenience and potential risks. The unified theory of acceptance and use of technology (UTAUT), the diffusion of innovations theory, and trust theory are employed to identify critical factors for promoting FRP adoption. A quantitative cross-sectional survey is conducted among smart hospital users in China, collecting 811 valid questionnaires, and the partial least squares structural equation method (PLS-SEM) is utilized for analysis. The results show that performance expectancy, effort expectancy, social influence, and facilitating conditions positively affect behavioral intention. Privacy concerns and perceived risks negatively impact trust in FRP, while familiarity enhances trust. Trust in FRP and personal innovativeness positively influence behavioral intention, with personal innovativeness moderating the trust-behavioral intention relationship. The findings emphasize the mediating role of trust in FRP and the importance of familiarity and personal innovativeness in driving FRP adoption. Gender (male or female) does not significantly impact the relationships and path coefficients in the model. However, slight discrepancies are observed between the permutation test and Henseler’s MGA in terms of the effect of privacy concerns on trust in FRP. This research contributes to the literature on users’ behavioral intentions, aiding smart hospitals in promoting FRP adoption while considering user concerns.